The effect of left ventricular pacing on transmural activation delay in myopathic human hearts. Issue 4 (20th January 2017) - Porta-Sánchez, Andreu; Angaran, Paul; Massé, Stéphane; Nair, Krishnakumar; Farid, Talha; Umapathy, Karthikeyan; Asta, John; Gizurarson, Sigfus; Nanthakumar, Kumaraswamy
Abstract: Aims: Left ventricular (LV) epicardial pacing (LVEpiP) in human myopathic hearts does not decrease global epicardial activation delay compared with right ventricular (RV) endocardial pacing (RVEndoP); however, the effect on transmural activation delay has not been evaluated. To characterize the transmural electrical activation delay in human myopathic hearts during RVEndoP and LVEpiP compared with global epicardial activation delay. Methods and results: Explanted hearts from seven patients (5 male, 46 ± 10 years) undergoing cardiac transplantation were Langendorff-perfused and mapped using an epicardial sock electrode array (112 electrodes) and 25 transmural plunge needles (four electrodes, 2 mm spacing), for a total of 100 unipolar transmural electrodes. Electrograms were recorded during LVEpiP and RVEndoP, and epicardial (sock) and transmural (needle) activation times, along with patterns of activation, were compared. There was no difference between the global epicardial activation times (LVEpiP 147 ± 8 ms vs. RVEndoP 156 ± 17 ms, P  = 0.46). The mean LV transmural activation time during LVEpiP was significantly shorter than that during RVEndoP (125 ± 44 vs. 172 ± 43 ms, P  < 0.001). During LVEpiP, of the transmural layers endo-, mid-myocardium and epicardium, LV endocardial layer was often the earliest compared with other transmural layers. Conclusion: In myopathic human hearts, LVEpiP did not decrease global epicardial activation delays compared with RVEndoP. LV epicardial pacing led to early activation of the LV endocardium, revealing the importance of the LV endocardium even when pacing from the LV epicardium.